High-sensitivity cardiac troponin T is associated with disease activity in patients with inflammatory arthritis - Nguyen, Thao H. P.; Fagerland, Morten Wang; Hollan, Ivana; Whist, Jon Elling; Feinberg, Mark W.; Agewall, Stefan (PloS one, 2023)
To investigate whether high-sensitivity cardiac troponin T (hsTnT) correlates to markers of disease activity in inflammatory arthritis (IA), and whether antirheumatic treatment influences hsTnT levels. We assessed 115 patients with active IA (64 rheumatoid arthritis (RA), 31 psoriatic arthritis and 20 ankylosing spondylitis) before and after using methotrexate (MTX) alone or tumor necrosis factor inhibitor (TNFi) with or without MTX co-medication (TNFi±MTX). All patients starting with TNFi had been previously unsuccessfully treated with MTX monotherapy. HsTnT (measured in serum by electro-chemiluminescence immunoassay (Roche Elecsys® Troponin T- high-sensitivity)), and other clinical and laboratory parameters were evaluated at baseline, and after 6 weeks and 6 months of treatment. Of markers of disease activity, baseline levels of hsTnT positively correlated with Physicians' Global Assessment Score of disease activity in the total patient cohort (p = 0.039). In RA group, hsTnT positively correlated with swollen joints, Disease Activity Score for 28 joints with ESR and serum tumor necrosis factor levels (p = 0.025, p = 0.008, p = 0.01, respectively). Median hsTnT at baseline was 5.0 ng/L, and did not change significantly at 6-week visit (6.0 ng/L, p = 0.37) and 6-month visit (6.0 ng/L, p = 0.18) with either antirheumatic therapy. HsTnT levels were associated with inflammatory markers for IA disease activity. However, while inflammatory markers significantly improved after antirheumatic treatment, hsTnT did not change during the 6-month follow-up period.